Beyond Dopamine: GABA, Glutamate, and the Axial Symptoms of Parkinson Disease - O'Gorman Tuura, Ruth L.; Baumann, Christian R.; Baumann-Vogel, Heide (Frontiers in Neurology, 2018)
Introduction: The axial symptoms of Parkinson disease (PD) include difficulties with balance, posture, speech, swallowing, and locomotion with freezing of gait, as well as axial rigidity. These axial symptoms impact negatively on quality of life for many patients, yet remain poorly understood. Dopaminergic treatments typically have little effect on the axial symptoms of PD, suggesting that disruptions in other neurotransmitter systems beyond the dopamine system may underlie these symptoms. The purpose of the present study was to examine the relationship between the axial symptoms of PD and GABA and glutamate levels quantified with magnetic resonance spectroscopy. Methods: The participant group included 20 patients with PD and 17 healthy control participants. Water-scaled GABA and Glx (glutamate + glutamine) concentrations were derived from GABA-edited MEGA-PRESS spectra acquired from the left basal ganglia and prefrontal cortex, and additional water-scaled Glx concentrations were acquired from standard PRESS spectra acquired from the pons. Spectra were analysed with LCModel. The axial symptoms of PD were evaluated from subscales of the Unified Parkinson’s Disease rating scale (MDS-UPDRS). Results: PD patients demonstrated significantly higher GABA levels in the basal ganglia, which correlated with the degree of gait disturbance. Basal ganglia Glx levels and prefrontal GABA and Glx levels did not differ significantly between patient and control groups, but within the PD group prefrontal Glx levels correlated negatively with difficulties turning in bed. Results from an exploratory subgroup analysis indicate that the associations between GABA, Glx and axial symptoms scores are typically more prominent in akinetic-rigid patients than in tremor-dominant patients. Conclusion: Alterations in GABAergic and glutamatergic neurotransmission may contribute to some of the axial symptoms of PD.